Theoretical and experimental analysis of an electromagnetic seismic isolation system. (1st January 2022) - Lin, Ging-Long; Lin, Chi-Chang; Li, Yi-Huan; Lin, Tzu-Ting
Highlights: An Electromagnetic Seismic Isolation System (EMSIS) was tested and analyzed. Both near-fault and far-field earthquakes were imposed on the EMSIS via a shaking table. The rotational electromagnetic (EM) damper addresses the stroke limitation. The equivalent EM damping ratio of the EMSIS was calibrated via sine sweep tests. The theoretical results were consistent with the experimental results, which confirmed the accuracy of the test results and the developed mathematical model of the EMSIS. Abstract: A near-fault (NF) ground motion with a strong velocity pulse component can induce considerable base displacement and structural acceleration in a base-isolated structure. Conventional viscous dampers are typically used to reduce the excessive responses of a seismic base-isolated system. It is generally recognized that the manufacturing tolerance requirements and costs of a long-stroke damper are higher than those of a typical viscous damper due to the buckling criterion. Thus, to satisfy the large stroke and high damping requirements of isolation systems in NF regions, an electromagnetic seismic isolation system (EMSIS) were developed in this study. The rotational electromagnetic (EM) damper addresses the stroke limitation. The mathematical model and theoretical formulas of the EMSIS were first established. Next, a prototype EMSIS was manufactured and its performance was validated using a shaking table apparatus. The equivalent EM damping ratio of the EMSIS was calibrated using a series of sine sweep tests. The test results indicated that each EM damper could provide a damping force proportional to the relative velocity of its two ends. Thus, the EM damper behaved as a linear viscous damper, which is suitable for seismic isolation systems. Finally, the EMSIS was subjected to both NF and far-field (FF) ground motions. The theoretical results were in agreement with the experimental findings. The shaking table test results revealed that the EM damper can effectively mitigate the displacement and acceleration responses of the developed isolation system under NF ground motions.